2014
DOI: 10.4056/sigs.4948668
|View full text |Cite
|
Sign up to set email alerts
|

Non-contiguous finished genome sequence and description of Sulfurimonas hongkongensis sp. nov., a strictly anaerobic denitrifying, hydrogen- and sulfur-oxidizing chemolithoautotroph isolated from marine sediment

Abstract: Here, we report a type strain AST-10 representing a novel species Sulfurimonas hongkongensis within Epsilonproteobacteria, which is involved in marine sedimentary sulfur oxidation and denitrification. Strain AST-10T (= DSM 22096T = JCM 18418T) was isolated from the coastal sediment at the Kai Tak Approach Channel connected to Victoria Harbour in Hong Kong. It grew chemolithoautotrophically using thiosulfate, sulfide or hydrogen as the sole electron donor and nitrate as the electron acceptor under anoxic condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 23 publications
1
28
0
Order By: Relevance
“…P. pantotrophus , Rhodopseudomonas palustris , Rhodovulum sulfidophilum and Starkeya novella ), which carry the soxABCDXYZ genes in a single gene cluster (Ghosh and Dam, ), Sulfurimonas spp. contain two separate sox clusters, that is, soxXY 1 Z 1 AB and soxCDY 2 Z 2 (Sievert et al ., ; Sikorski et al ., ; Grote et al ., ; Cai et al ., ). Both clusters contain homologues of soxYZ , which show a high level of divergence and are proposed to be involved in oxidation of different sulfur compounds (Meier et al ., ; Pjevac et al ., ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…P. pantotrophus , Rhodopseudomonas palustris , Rhodovulum sulfidophilum and Starkeya novella ), which carry the soxABCDXYZ genes in a single gene cluster (Ghosh and Dam, ), Sulfurimonas spp. contain two separate sox clusters, that is, soxXY 1 Z 1 AB and soxCDY 2 Z 2 (Sievert et al ., ; Sikorski et al ., ; Grote et al ., ; Cai et al ., ). Both clusters contain homologues of soxYZ , which show a high level of divergence and are proposed to be involved in oxidation of different sulfur compounds (Meier et al ., ; Pjevac et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Currently sequenced genomes of Sulfurimonas spp. suggest that the oxidation of reduced sulfur compounds likely involves the SOX system as well as different types of SQR enzymes (Sievert et al ., ; Sikorski et al ., ; Grote et al ., ; Cai et al ., ; Han and Perner, ). Unlike many alphaproteobacterial sulfur oxidizers (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Weerakoon and Olson (2008) also showed that this unusual mechanism is due to differences in the NuoE/F subunits that interact with NADH in canonical complex I. Interestingly, they note that S. denitrificans and other autotrophic Epsilonproteobacteria also possess non-canonical NuoEF subunits. So far, this different NuoEF composition has also been observed in all genomes of Sulfurimonas and Sulfurovum sequenced to date (Nakagawa et al, 2007;Sievert et al, 2008;Sikorski et al, 2010;Grote et al, 2012;Cai et al, 2014)…”
Section: Reverse Electron Transportmentioning
confidence: 99%
“…In contrast to the Nautiliales, nearly all Campylobacterales isolates reported thus far have the potential to use oxygen, and in some cases tolerate levels approaching atmospheric concentrations Takai et al, 2006). Even for those reported to be strict anaerobes, genome sequences contain a cbb 3 -type high-affinity cytochrome c oxidase (Grote et al, 2012;Cai et al, 2014), suggesting the ability to use oxygen as an electron acceptor is typical of autotrophic Campylobacterales. The use of nitrate and sulfur as electron acceptors is also common in this lineage but obligate aerobes do exist .…”
Section: 3mentioning
confidence: 99%
“…Although type II to VI sqr genes were detected in the different genome-sequenced Sulfurimonas species (20,22,(39)(40)(41), no experimental evidence for a functional SQR in Sulfurimonas currently exists. S. denitrificans harbors three sqr-homologous genes, Suden_2082, Suden_1879, and Suden_619, which encode type II, III, and IV SQRs, respectively (20,22).…”
Section: Growth Of S Denitrificans On Sulfidementioning
confidence: 99%